Interaction of miR-200a-3p with YAP regulates cell proliferation and metastasis differentially in HPV-positive and HPV-negative cervical cancer cells - Hong Chen; Lingling Gu; Min Zhang; Huifen Chen; Hong Liao; Xueping Cao; Lu Yu; Jun Zhang (figshare, 2022)
Abstract Background Although evidence has revealed that miR-200a-3p is involved in the malignant progression of various tumors, the regulatory mechanism of miR-200a-3p in the development of cervical cancer (CC) cells with different HPV statuses remains unknown. The present study was to investigate the differential effects of either miR-200a-3p or YAP on tumorous cells’ fate in vitro in HPV-negative and HPV-positive cervical cancer cell models, and to explore if the changes in proliferation, migration, and invasion of the CC cells with different HPV statuses could be attributed to the differential interactions between miR-200a-3p and YAP. Methods The colony formation assays, EDU assays and Transwell assays were performed for CC cell proliferation, migration and invasion capacities analysis. The prediction of downstream targets of miR-200a-3p was performed by bioinformatical databases. The dual-luciferase reporter assays were used to validate the binding sites of miR-200a-3p and YAP. The qRT-PCR assays were performed to quantify the mRNA expression of miR-200a-3p and YAP, and the protein levels of YAP were examined by Western blot analysis. Results The results demonstrated that miR-200a-3p overexpression suppressed proliferation, migration, and invasion of the HPV-negative C33A cells but promoted the growth and metastasis of HPV-positive CC cells, while YAP promoted the cell growth and metastasis not only in HPV-negative but also in the HPV-positive CC cells. The suppressive role of miR-200a-3p in C33A cells appeared to be mediated partially by direct interaction with YAP, and YAP might participate in miR-200a-3p-mediated cellular changes in CC cells differing from not only the presence or absence of HPV but even also the subtypes of HPV of CC cells. Meanwhile, we preliminarily revealed that the expression level of miR-200a-3p was significantly decreased in HPV-negative, but not in HPV16-positive cervical neoplasm mucus samples. Conclusion miR-200a-3p-mediated functional changes of YAP exhibited regulatory effects on cells’ fate differentially in HPV-negative and HPV-positive cervical cancer cells.
Keywords: Medicine; Cell Biology; Molecular Biology; Biotechnology; Biological Sciences not elsewhere classified; Developmental Biology; Cancer; Infectious Diseases; Virology